Practices Regarding Biomedical Waste Management Among Health Functionaries: A Rural Haryana Perspective - Suraj Chawla; Ramesh Verma; Pardeep Khanna (Medsci Publications, 2016)
Introduction: Waste generated from medical activities can be hazardous, toxic and even lethal because of their high potential for diseases transmission. Biomedical Waste (BMW) management is a legal necessity as well as social responsibility. Aims & Objectives: To assess practices regarding biomedical waste management among healthcare functionaries. Material and Methods: A list of all health care centres was obtained from CHC Dubaldhan and CHC, Dighal of block Beri. After obtaining informed consent, a pre-tested semi-structured interview schedule was administered to the study subjects and the responses were recorded by the investigator himself. Results: The segregation of BMW was inadequate in 20 (40.8%) government centers and 59 (96.7%) private centers. Hub-cutter/ needle destroyer was available at 31 (63.3%) of government health centers while only 12 (19.7%) of the private health centers possessed it. Disinfection was adequate in 3 (6.1%) government centers and 1 (1.6%) private center. Conclusion: The study has shown that appropriate biomedical waste management and safe handling practices were lacking among health functionaries and condition in private centers was significantly poorer than government centers in this regard.